Pola Asuh Pendidikan Bagi Anak Terhadap Perkawinan Beda Agama Sebagai Studi Pendidikan Agama Kristen di Kota Tarakan - Saap, Sadrakh Wicaksono; Sopakua, Samel; Rumahuru, Yance Z (INSTITUTIO : JURNAL PENDIDIKAN AGAMA KRISTEN, 2023)
Educational parenting patterns for children in interfaith marriages certainly have an impact on children's understanding of religious identity and interactions with the surrounding environment. Through a qualitative approach and interviews with parents in interfaith marriages, this research tries to understand parents' experiences in raising children in the context of religious differences. Parents in interfaith marriages face challenges in raising children. Religious differences can influence the religious education given to children, with some families choosing to provide dual religious education or following the religion that is more dominant in the family. Children experience identity confusion, have difficulty understanding religious differences, and face challenges in interacting with those around them who have different religious beliefs. The contribution of this research to the understanding of child education parenting patterns in interfaith marriages is by providing in-depth insight into the challenges faced by parents and their impact on children. The implications of this research for the education of children in interfaith marriages include the importance of open communication, inclusive approaches, and introducing children to various religions. This research provides practical guidance for parents in interfaith marriages as well as educational stakeholders to create an inclusive environment and support children's development in the context of religious differences.Keywords: parenting style, children's education, interfaith marriages, Christian religious education.